Chronic inflammation in hemodialysis patients with secondary hyperparathyroidism - Dudar, I.O.; Loboda, O.M.; Dudar, S.L.; Savchuk, V.M. (Ukrainian Journal of Nephrology and Dialysis, 2022)
Abstract. Our study aimed to establish a possible correlation between parathyroid hormone (PTH) levels and biomarkers of inflammation in hemodialysis patients with secondary hyperparathyroidism. Methods. This observational сross-sectional study involved 108 hemodialysis patients with secondary hyperparathyroidism. The levels of serum cytokines interleukin-1 (IL-1), IL-6 and tumor necrosis factor-alpha (TNF-alpha) were determined in all patients. The correlations between the levels of inflammatory mediators on the one hand and the level of PTH on the other were studied. The effects of diabetes, heart failure (HF), fractures, and smoking on the inflammatory status and PTH levels were assessed. Results. The level of IL-1 in patients with diabetes was more than 2 times higher than in patients without diabetes (p<0.05). The level of IL-6 in patients with diabetes was more than 3 times higher than in patients without diabetes (p<0.05). The level of TNF-alpha in patients with diabetes was more than 1.5 times higher than in patients without diabetes (p<0.05). The level of PTH was more than 2.4 times higher in patients with diabetes compared with patients without diabetes (p<0.05). The level of IL-1 in patients with HF was 1.7 times higher than that in patients without HF (p<0.05). The level of IL-6 in patients with HF was more than 3 times higher than in patients without HF (p<0.05). The level of TNF-alpha did not differ significantly in patients with and without HF. The level of PTH was more than 2.3 times higher in patients with HF compared with patients without HF (p<0.05). The level of IL-1 in patients with fractures was more than 2.8 times higher than in patients without fractures (p<0.05). The level of IL-6 in patients with fractures was more than 3.6 times higher than in patients without fractures (p <0.05). The level of TNF-alpha in patients with fractures was more than 1.5 times higher than in patients without fractures (p<0.05). The level of PTH was more than 2.4 times higher in patients with fractures compared to patients without fractures (p<0.05). Smoking status in our study did not affect the levels of both PTH and inflammatory mediators. A positive correlation between the concentration of IL-6 and serum PTH was found (r = 0.7; p <0.001). Conclusions. The presence of chronic inflammation is characteristic of hemodialysis patients with secondary hyperparathyroidism. Proinflammatory cytokine levels are significantly higher in patients with diabetes, HF, and a history of fractures. A positive correlation between the level of IL-6 and PTH may indicate a relationship between the development of secondary hyperparathyroidism and chronic inflammation.